If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p = 18 + -1(2 + -3p) p = 18 + (2 * -1 + -3p * -1) p = 18 + (-2 + 3p) Combine like terms: 18 + -2 = 16 p = 16 + 3p Solving p = 16 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. p + -3p = 16 + 3p + -3p Combine like terms: p + -3p = -2p -2p = 16 + 3p + -3p Combine like terms: 3p + -3p = 0 -2p = 16 + 0 -2p = 16 Divide each side by '-2'. p = -8 Simplifying p = -8
| 49s-26=107 | | 6x-(5+2x)+5=x | | 5(p-1)=p+5 | | 5/8÷25/16= | | 2-4x=3x-5 | | e(2x+1)+7e(x)-15=0 | | 7x=31412+312 | | 36t^2+128t^3=9 | | -36t^2+128t^3=9 | | 5+3=x-3x-2x | | -72*t^2+256*t^3=18 | | x^10=1.55 | | x^10=15 | | 140x+x=180 | | -4x^3=-4x | | -2+a-b+1=0 | | 1+a+2b+4=0 | | x+4*3-4=65 | | (x-9)(x-12)=0 | | a=bx+cx^3 | | 7x-2y+4=o | | 2x-8x+13=26-x+14 | | 4-4x=4x+4 | | 3a+3b-2ab=0 | | 16-3x=11-21x | | 8-6x=9+x | | 13+7x=6-7x | | 8(3x-8x)(4x+9)=0 | | 14x-9=5x | | 17x-3=3x+11 | | 14x-9x=5x | | 29x=9+2x |